Optimalisasi Perawat Sehat dalam Memberikan Pelayanan Keperawatan Bermutu - Endang Sudjiati; Hanny Handiyani; Krisna Yetti; Cori Tri Suryani (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to develop guidelines and provide an overview to optimize the health of nursing staff in public hospitals in Jakarta. This research method uses a pilot project starting from data collection, problem analysis, problem priority setting, preparation of a plan of action, implementation and evaluation. Research respondents were 54 room heads and 479 nursing staff. Problem analysis was performed using a fishbone diagram. The results of the analysis show that there is a problem in the form of not optimal adoption of healthy nurse behavior due to the absence of a guide for healthy nurses, the SPO has not been compiled and there are still nurses who do not know about the behavior of healthy nurses. In conclusion, the solution to the problem is to draft a guide for healthy nurses in the hospital. Keywords: Health Optimization, Guidelines for Healthy Nurses, Nursing Staff